Rural healthcare workers views on the introduction of solar power and oxygen concentrators in health facilities in Papua New Guinea: a qualitative study - Francis Pulsan; Trevor Duke; John Vince (James Cook University, 2021)
Introduction: A motivated, well supported rural health workforce is required to provide appropriate child health services to the rural population. This study explored the views of rural health workers in Papua New Guinea on the impact of a program to improve oxygen delivery systems and to provide reliable power to their health facilities. Methods: A pre-tested, self-administered open question survey was carried out among rural health workers from 38 health facilities in which oxygen concentrators had been installed, including 30 with solar power. Thematic analysis was carried out on the responses. Results: The program was highly appreciated. Benefits extended beyond the ability to treat children with a reliable source of oxygen. Participants reported the positive community response to improved patient care and avoiding patient referrals. They stressed their wish for further improvements in infrastructure and for continuing education. Conclusion: The program improved morale and job satisfaction. The views of rural health workers are important in assessing program effectiveness.